Retinal and Cortical Contributions to Excessive V1 Neuron Firing Rate Variability in Schizophrenia: A Computational Modeling Analysis - M. Silverstein, Steven; Kourtev, Hristiyan (Journal of Systems Biology, 2019)
Excessive variability in behavioral performance and neuronal activation is a common finding in studies of schizophrenia. Recent evidence suggests that this may be due to an imbalance in the ratio of excitation to inhibition in brain function, or E/I imbalance. We used computational modeling of visual system activity to determine whether different potential causes of E/I imbalance would generate effects resembling those reported in schizophrenia. Three major findings emerged. First, reductions in retinal and lateral geniculate nucleus signaling initially led to increases in firing rate variability within the context of reduced V1 activation; however, with prolonged adaptation to weakened sensory signaling, compensatory hyper-activation in V1 neurons occurred, but variability was no longer increased. Second, direct increases in V1 excitation, or decreases in inhibition, led to the highest levels of initial activation but not variability; however, with prolonged inhibitory adaptation to increased excitation, overall activity was no longer elevated, but an increase in firing rate variability was observed. Third, the greatest fluctuation in firing rate variability, in response to the same stimulus across increasing contrast levels, was observed with reductions in sensory signaling, but only immediately after model perturbations; with prolonged adaption, the largest fluctuations were associated with increased excitation or reduced inhibition within V1. Implication of these findings are that schizophrenia-related increases in neuronal response variability may arise from at least two sources: 1) weakened sensory signaling and its associated low signal-to-noise ratio; and 2) compensatory but incomplete inhibitory responses to continuous increases in cortical excitation.
Keywords: V1; Schizophrenia; Excitation-Inhibition balance; Computational Psychiatry; Vision; Variability; Retina; LGN.